Smart Tourism Development through QRIS Adoption among MSMEs - Novita Herlissha; Tiara Fitari; Abdul Hafiz (Sean Institute, 2026)
The development of smart tourism in tourism villages requires the integration of digital services that enhance efficiency, accessibility, and visitor experience. One essential component of smart tourism is the adoption of digital payment systems supported by adequate digital financial literacy among local micro, small, and medium enterprises (MSMEs). Batu Belubang Tourism Village has significant tourism potential; however, most MSME actors still rely on cash-based transactions due to limited understanding of digital financial services. This community service program aims to improve digital financial literacy and support the implementation of the Quick Response Code Indonesian Standard (QRIS) among MSMEs as part of smart tourism development. The program employed a direct, door-to-door assistance method using a participatory approach, involving lecturers and students as facilitators. Activities included individual socialization, technical assistance for QRIS registration, and initial implementation guidance. The results indicate a notable improvement in MSMEs’ understanding of digital payment systems and a positive attitude toward QRIS adoption. MSME actors began to recognize QRIS as a tool that supports transaction efficiency, financial transparency, and tourist convenience. This program contributes to strengthening the digital ecosystem of tourism villages and supports the sustainable development of smart tourism at the local level